Hope matters : why changing the way we think is critical to solving the environmental crisis - Kelsey, Elin (Greystone Books, 2020)
"Hope Matters boldly breaks through the narrative of doom and gloom to show why evidence-based hope, not fear, is our most powerful tool for change. Kelsey shares real-life examples of positive climate news that reveal the power of our mindsets to shape reality, the resilience of nature, and the transformative possibilities of individual and collective action. And she demonstrates how we can build on positive trends to work toward a sustainable and just future, before it's too late." -- Amazon.com.